The analysis of composite beams with partial interaction using the general technique method - Chung, Nguyen Van; Thanh, Bui Cong (Vietnam Journal of Mechanics, 2008)
This paper presents a modeling technique that derives from the work of Newmark to describe the behavior of steel-concrete composite beams with elastic shear connection. The model is used to derive expressions for beam curvature, rotation and deflection under monotonic load from which the stiffness matrix is derived and finite element analysis performed on a set of illustrative examples. Model results are compared to those obtained using other method.